Characterization and modeling of surface defects in EP3D printing (2015)
Purpose This paper aims to report an experimental study of how surface defects evolve in EP3D printing as more layers are accumulated and proposes a simulation model for the process. Design/methodology/approach A series of measurements on the surface roughness were taken layer-by-layer for two 30-layer samples. A model of the process was constructed based on dynamic system modeling, system identification techniques and the analysis of the measurements from the samples. Findings The transient response of the fuser has a significant impact on the surface of the print. The surface of the EP3D printed part depends heavily on the compliance of the interface. The model developed is able to approximate the behavior of the surface as more layers are deposited. Research limitations/implications The model requires tuning multiple parameters, especially the compliance threshold for the interface; similar experiments/measurements are needed for any change in the system. Practical implications The simulation model provides a way to evaluate different process parameters and conditions that otherwise would be difficult and expensive to test. Originality/value This work provides better understanding into the limitations of EP3D printing process and provides a tool to find countermeasures to achieve successful EP3D prints.